Estimating regional land subsidence in Mehsana urban block, Gujarat: Effect of groundwater induced aquifer compaction. (2022) - Aggarwal, Ashish; Srivastava, P.K.; Gupta, D.K.; Chatterjee, R.S.
Abstract: Aquifer compaction due to excessive withdrawal of groundwater has led to land subsidence in many regions worldwide. Aquifer-System compaction is a function of the piezometric head, the depth of the total aquifer system and the hydrogeological characteristics of the aquifer. The present work is an attempt to characterize the land subsidence caused due to aquifer system compaction in parts of Mehsana city, Gujarat during two individual study periods of 2007 to 2011 and 2012 to 2017. Studies were undertaken for an observation well for which complete time series piezometric water level data was available for both pre and post-monsoon seasons. Elastic and Inelastic compaction were calculated from the piezometric data. The thickness of the aquifers and confining layers were taken from secondary data sources. The results show that there has been a considerable cumulative subsidence in the region during the period 2007 to 2011 with an average rate of 1.18 cm/yr. which declined to an average rate of 0.68 cm/yr. during 2012–2017. Such studies prove useful for monitoring land deformations due to excessive pumping as well as administration of groundwater resources especially in regions facing heavy declines of ground water.